Humic acid and boron treatment to mitigate salt stress on the melon plant - Osama Abd El-Salam SHALABY; Mohamed Moustafa EL-MESSAIRY (Acta Agriculturae Slovenica)
Salinity is one of the main abiotic stress factors which limit the growth and productivity of plants, however, the nutritional status of plants is the first brick in the resistance wall against stresses. Therefore, a factorial experiment was undertaken to investigate effects of soil applied humic acid (0, 7, 14, 21 l.ha-1) and boron foliar spraying (0, 50, 100 ppm) and their interaction on growth and yield of melon plant under saline conditions. The results suggested that the treatments soil application of humic acid and the boron spraying successfully mitigated the deleterious effects of salt stress and influenced growth and yield of melon plant. Humic acid at 21 l.ha-1 or boron spray at 50 ppm exhibited an improvement in growth and yield of melon, in terms of plant length, plant fresh and dry mass, chlorophyll (SPAD), fruit mass, total yield, and also leaf nutrient content (N and K) and total soluble solids (TSS) of fruits, while reduced the sodium content of leaves. The combined treatment of humic acid at 21 l.ha-1 and boron spraying at 50 ppm was found to be more effective for the melon plant to improving growth performance and the crop yield by 21 % as compared with the control group under saline conditions.